Aging affects the in vivo regenerative potential of human mesoangioblasts. Issue 2 (4th February 2018) - Rotini, Alessio; Martínez‐Sarrà, Ester; Duelen, Robin; Costamagna, Domiziana; Di Filippo, Ester Sara; Giacomazzi, Giorgia; Grosemans, Hanne; Fulle, Stefania; Sampaolesi, Maurilio
Summary: Sarcopenia is the age‐related loss of muscle mass, strength, and function. Although the role of human satellite cells (SCs) as adult skeletal muscle stem cells has been deeply investigated, little is known about the impact of aging on muscle interstitial stem cells. Here, we isolated the non‐SC CD56 – fraction from human muscle biopsies of young and elderly subjects. The elderly interstitial cell population contained a higher number of CD15 + and PDGFRα + cells when compared to young samples. In addition, we found that the CD56 – /ALP + cells were well represented as a multipotent stem cell population inside the CD56 – fraction. CD56 – /ALP + /CD15 – cells were clonogenic, and since they were myogenic and expressed NG2, α‐SMA and PDGFRβ can be considered mesoangioblasts (MABs). Interestingly, elderly MABs displayed a dramatic impairment in the myogenic differentiation ability in vitro and when transplanted in dystrophic immunodeficient Sgcb‐null Rag2‐null γ c‐null mice. In addition, elderly MABs proliferated less, but yet retained other multilineage capabilities. Overall, our results indicate that aging negatively impacted on the regenerative potential of MABs and this should be carefully considered for potential therapeutic applications of MABs.